EFL teachers’ online teacher professional development experiences amidst the COVID-19 pandemic: Practices and perceptions - Atmojo, Arief Eko Priyo (Englisia: Journal of Language, Education, and Humanities, 2021)
This research investigates the EFL teachers’ practices and perceptions of online teacher professional development (OTPD) experiences to improve their competencies for teaching online language learning amidst the COVID-19 pandemic. 42 EFL teachers voluntarily became the participants through invitation. All participants were requested to give responses on a questionnaire. Eight participants were then invited for an individual semi-structured interview. Descriptive statistics were employed to analyze the questionnaire data, whilst qualitative coding was used to analyse the interview data. The results reveal many important findings regarding EFL teachers’ practices and perceptions of experiencing OTPD amidst the COVID-19 pandemic. The findings are beneficial to help OTPD designers and providers, policy makers, and school leaders provide OTPD which best fits EFL teachers’ needs, preferences, and teaching contexts.